The Effect Of Service Quality And Price On Customer Satisfaction At Tony's New York Pizza - Kurniawati, Natalia Sri Endah; Kaka, Karolina Ina; Joshua, Jatmiko Wahyu Nugroho (JAKADIKSI: JURNAL VOKASI, 2025)
Factors determining customer satisfaction include Service Quality and Price. The problem in this study is whether service quality and price affect customer satisfaction at Tony's New York Pizza. This study aims to determine the effect of service quality and price on customer satisfaction at Tony's New York Pizza restaurant. The location of this research is Jalan Bumbak No.110B, Kerobokan, North Kuta, Badung, Bali. The independent variables in this research are quality and price while the dependent variable is customer satisfaction. This research uses quantitative methods. The method of collecting data are documentation, questionnaires and observation. The sampling technique used was purposive sampling technique as many as 106 respondents. The data analysis technique used is the Multiple Linear Regression test. Based on the research results, it is known that: (1) Service Quality has a positive and significant effect on customer satisfaction of 0, 229 with a significant level of 0.000. (2) Price has a positive and significant effect on customer satisfaction of 0.506 with a significant level of 0.000. (3) Service quality and price have a significant positive effect of 432,149 with a significant level of 0.000. The influence of service quality and price on customer satisfaction is 90.4%.